The Effect of Demographic Factors on Risk Tolerance and Investment Instrument Choice: Evidence From Indonesian Investors - T Muhammad Jumeil; Desy Asmara (CV. Civiliza Publishing, 2026)
Traditional economics portrays investors as rational decision-makers, but this assumption doesn’t always true. Investment decisions are shaped by various factors, one of which is the investor's demographic profile. This study aimed to ascertain whether differences exist in risk tolerance levels and the selection of investment instruments among investors based on demographic variables. Data were gathered through an online questionnaire. The findings reveal significant differences in risk tolerance levels correlated with the demographic variables of age and marital status. Additionally, the results indicate variations in the selection of investment instruments based on the demographic factors of gender, education, and income.